Perilaku Pacaran dan Faktor-Faktor yang Mempengaruhi Seks Pranikah pada Remaja di Sikka Flores: Dating Behavior and Factors Affecting Premarital Sex in Adolescents in Sikka Flores - Nababan, Sudarwati (Stikes Wira Medika Bali, 2020)
Adolescence is a transitional period, fastest physic changes, sometimes is not balance with the mental changes, this problem can bring teenegers to premarital sexual behaviour not responsible. Survey results of adolescent sexual behaviour in Sikka district in 2017, adolescents aged 12 to 24 years who are not married and have had sexual intercourse as much as 35%, this percentagr is higher than the national percentage which is 10%. Data from Kota Uneng village in 2019, teenagers often hang out on the stone revetment while watching porn, there were 12 unwanted pregnancies cases. The aims of the research to explore the factors that influence dating behaviour and premarital sexin adolescent. The methods be used in this research is analytic observation with cross-sectional design. The sample of this study consists of 200 teenagers in Kota Uneng village,14-21 years old, the have a boyfriend or girlfriend selected by using proportional stratified random sampling. Data was collected using face to face interview. Data were then analysed with chi-square test and logistic regression method. This research found there is a relationship between knowledge of premarital sexual (p=0,005), access to pornographic media (p=0,000), family support (p=0,037), culture value (p=0,006), with dating behaviour and premarital sexin to the adolescent. The better religion understanding does not make adolescents to influenced (p=0,292). Adolescents who access pornography are 0,019 times more often possible to doing a mistaken dating behaviour than compared with the adolescents who don’t. Conclusion, Accessing pornography was the most significant factor related to premarital sexin behaviour in the Kota Uneng village.